Uji Praklinis Efek Anti Inflamasi dan Toksisitas Fraksi Aktif Spilanthes Paniculata Wall & Dc - Djamain, Armi; Almahdy, Almahdy; Adnan, Adek Zamrud (Fakultas Farmasi Universitas Andalas, 2012)
The aim of this study was to evaluate an antiinflamation effect of S.paniculata and Siabadicencis extracts at the dose of 300 mg/200 g BW by induction of rats paw edema. Edema condition was induced by administration of 0,2 ml aqueous solution of 0,1 % carrageenan. This was followed by the assay of antiinflamatory effect of fractionated S. paniculata extract with hexane, DCM, ethyl acetate and butanol respectively. A decrease in rats paw edema volume was measured after treatments. Results showed that percent inhibition of inflammation after administration of Siabadicencis, S. paniculata extracts and positive control were 35;48 and 63 % respectively, while that of the hexane, DCM, ethyl acetate and butanol fraction was 69, 27, 53, and 43 % respectively. The antiinflamation effect of the hexane fraction was then determined at various doses (10 ; 20 and 30 mg/20 g BW with positive control acetosal 1,3 mg/20 g BW, by induction of rat back edema. The edema was induced by administration of 1 % carrageen in sessame oil at day 0 (0,1 ml) and day 1 st (0,5 ml) respectively. Parameters such as edema volume, haemoglobin and haematocrit were observed. Results indicated that percent inhibition of inflammation diameter after administration of the fraction at doses  10, 20, 30 mg/20 g BW and acetosal 1,3 mg/20 g BW on day 5th was 11 ; 15 ; 17 ; and 20 % respectively. While percent inhibition of inflammation volume of those groups were 19, 38, 62 and 63 % respectively the haemoglobine (Hb) of dose group 10, 20, 30 mg/20 g BW and negative control was 14.808 ; 15.117 and 12.944 g/dL respectively and 45,25 that of control positive 44,2 respectively. The mean value of necrosis hepatocyte at 3 sites of dose group 30 mg/20 g BW, positive and negative control groups was 6,38 ; 13,82 and 3,55 respectively.